THE ANALYSIS OF CONTRACTOR SELECTION PRIORITY DETERMINATION FOR THE LONG SEMAMU – LONG BAWAN 2 ROAD CONTRUCTION PROJECT, NORTH KALIMANTAN - Nugraha, Coki Adianta; Oetomo, Wateno; Muhammadun, Haris (Transpublika Publisher, 2022)
Road construction is one of the fulfillment of the government's duties in providing mobility facilities for people's land transportation to move from one place to another. The government, through contractors as road construction implementers, must work carefully, so it is important for the government to select road construction contractors who meet predetermined criteria so that the road construction process can take place optimally. This study aims to find priority criteria and alternative contractors in the process of selecting Long Semamu – Long Bawan Road Construction Contractors. This study uses a quantitative descriptive approach with the aim of determining the Criteria and Alternative Variables. The population of this study were employees of the Public Works Department as the Tender Team for the Selection of Road Construction Contractors as many as 32 people with the research sample being the total population. Data collection techniques were carried out by distributing questionnaires and interviews. Data analysis techniques for research aids use the AHP method with AHP data processing software (Expert Choice version 11). The results of the study prove that the Price Criteria is a priority criterion in the selection of road construction contractors. In addition, Contractor C is an alternative priority in road construction.